1990
DOI: 10.3109/08977199009011004
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Tissue Factor by Interleukin-2 in Acute Myelogenous Leukemia (AML) Cells

Abstract: We investigated the induction of tissue factor by lymphokines in human monoblastic leukemia cell lines (U937) and leukemic cells from AML (acute myelogenous leukemia) patients. After incubation for 24 h, IL-2 enhanced the intracellular tissue factor 15-fold with U937 cells, and GM-CSF enhanced it 6-fold. In contrast, other lymphokines, such as IL-1-alpha, IL-1-beta, IL-3, IL-4 and G-CSF, did not affect the activity of tissue factor. The leukemic blasts, depleted of T-lymphocytes, taken from five out of 16 AML … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…ALL is the most common childhood malignancy and the second most common adult leukemia and AML is the second most common childhood malignancy. It was reported that TF is expressed on the human leukemic cell lines HL-60 [72,73,79,85,86], Molt-4 [87], THP-1 [11,87] and on leukemic cells from patients with AML [73,74,75,76,77,78] and ALL [79,80]. TF is not expressed on the normal peripheral mononuclear cells unless stimulated by endotoxin or other cytokines [72], nor on myeloid precursor cells [75].…”
Section: Tissue Factor Expression In Cancermentioning
confidence: 99%
“…ALL is the most common childhood malignancy and the second most common adult leukemia and AML is the second most common childhood malignancy. It was reported that TF is expressed on the human leukemic cell lines HL-60 [72,73,79,85,86], Molt-4 [87], THP-1 [11,87] and on leukemic cells from patients with AML [73,74,75,76,77,78] and ALL [79,80]. TF is not expressed on the normal peripheral mononuclear cells unless stimulated by endotoxin or other cytokines [72], nor on myeloid precursor cells [75].…”
Section: Tissue Factor Expression In Cancermentioning
confidence: 99%
“…26]. Tanaka and Kishi demonstrated that IL-2 increased the TF activity by 2.5 to 14-fold in leukemic blast cells, depleted of T-lymphocytes, taken from patients with acute myelogenous leukemia [84]. Recently, Stem and colleagues [85] identified a tumor-derived mediator (meth A) in murine methylcholantherene A fibrosarcoma cells.…”
Section: Induction Of Tissue Factor By Tumor Cell Mediatorsmentioning
confidence: 99%
“…If untreated, death usually occurs within 6 months in most cases. It was reported that TF is expressed on the human leukemic HL-60 (Freeburn et al, 1995;Kubota et al, 1991;Rickles et al, 1995;Tanaka et al, 1989), Molt-4 (Tanaka, 1989), THP-1 (Tanaka, 1989) cell lines , and on leukemic cells from patients with AML (Andoh et al, 1987;Bauer et al, 1989;Nakasaki et al, 2000b;Tanaka et al, 1989;Tanaka and Kishi, 1990;Tanaka and Yamanishi, 1993) and ALL (Kubota et al, 1991;Nakasaki et al, 2000a). TF is not expressed on the normal peripheral mononuclear cells unless stimulated by endotoxin or other cytokines (Rickles et al, 1995), nor on myeloid precursor cells (Bauer et al, 1989).…”
Section: Tf In Leukemiamentioning
confidence: 99%